Psychological Guidance of the Teachers Community the al-Qur'an Education Garden (TPQ) an-Nahdliyah at Metro City In Modifying Students' Behavior Through Positive Reinsforcement - Nailul Izzah; Muhammad Syaifullah (Yayasan Payungi Smart Madani, 2025)
Al-Qur'an education parks, commonly abbreviated as TPQ or TPA, are one of the non-formal educations that play a very important role in shaping personal character that has spiritual religious strength, a personality with noble morals considering that TPQ specifically teaches religious and religious education, where its role cannot be underestimated in the world of education. However, it is known that not a few students (santri) are also involved in deviant behavior from the norm. Among others, theft, fighting, robbery, going on strike, to playing truant. Going on strike & playing truant is a failure in development tasks. Because students have no intention of continuing to study or even not continuing to the next higher level and violating school rules, it is difficult to move towards a good future. From these problems, behavioral counseling with positive reinforcement techniques is one option to overcome the problem of playing truant and the desire to stop studying the Koran at TPQ when students enter junior high school. The approach uses Asset Based Community Development (ABCD) with the stages used in this mentoring activity being Inculturation, Discovery, Design, and Define. The results of community psychology mentoring of TPQ an-Nahdliyah teachers in Metro City in modifying students' behavior through Positive Reinforcement show changes in TPQ teachers' teaching patterns and understanding of Positive Reinforcement psychology theory. TPQ teachers' teaching patterns have changed where teachers give positive reactions to students' positive behavior with the aim of maintaining and improving that behavior.